Cooperative Member Performance Model Through Competency Collaboration and Digital Marketing in Pangandaran Regency, West Java, Indonesia - Joeliaty Joeliaty; Sri Djatnika; Vita Sarasi (Eduvest - Journal of Universal Studies, 2022)
This research aims to develop a problem-solving model by measuring the competence, digital marketing, and members’ performance of several cooperatives in Pangandaran Regency, West Java Province, Indonesia. This study uses quantitative methods with sequential explanation strategies through direct surveys to several cooperatives in Pangandaran Regency by conducting a structured questionnaire spread using closed questions taken from some literature using a Likert scale and some open-ended questions. Data analysis uses descriptive and verification uses t-test, ANOVA, and R square. This research was conducted to 100 members of cooperatives located in Pangandaran Regency. The reveal that the competence of cooperative members and digital marketing affect the achievement of cooperative members’ performance, both partially and simultaneously. Partially, the influence of cooperative members’ competence on the performance of cooperative members is 25,4%, while the influence of digital marketing on the performance of cooperative members is 8%. Simultaneously, it was found that the influence of cooperative members’ competence and digital marketing on the performance of cooperative members was 25,4% too.